Crossing the River - Eilati, Shalom, 1933- (Book collections on Project MUSE., 2008)
Crossing the River is a personal memoir-and more. Against the backdrop of Lithuania's occupation-first by the Red Army, next by the Germans, and then again by the Russians-it is a story reflected through the prism of a sharp-eyed young child, Shalom Eilati. His story starts in the occupied Kovno Ghetto and ends with his flight across the Soviet border, through Poland and Germany and finally, his arrival in Palestine. The adult survivor, while recalling the terrorized child that he was and how he then perceived the adult world, also takes stock of his present life. Th.